Implementing cognitive remediation therapy (CRT) in a mental health service: staff training. (April 2016) - Dark, Frances; Newman, Ellie; Harris, Meredith; Cairns, Alice; Simpson, Michael; Gore-Jones, Victoria; Whiteford, Harvey; Harvey, Carol; Crompton, David
Objective: This paper describes the establishment of training in cognitive remediation for psychosis within a community mental health service. Methods: Clinical staff working in the community of a mental health service were surveyed to ascertain their interest in cognitive aspects of psychosis and skills training in cognitive remediation (CR). Based on the results of the survey a tiered training programme was established with attendance figures reported for each level of training. Fidelity assessment was conducted on the five CR programmes operating. Results: Of 106 clinical staff working in the community with people diagnosed with a psychotic illness 51 completed the survey (48% response rate). The training needs varied with all 106 staff receiving the fundamental (mandatory) training and 51 staff receiving CR facilitator training. Thirty three percent of staff trained as facilitators were delivering CR. Conclusions: Up skilling the mental health workforce to incorporate an understanding of the cognitive aspects of psychosis into care delivery can be facilitated by a tiered training structure. Fundamental training on the psychosocial aspects of psychosis can act as a platform for focussed CR skills based training. There is also a need for accessible therapy based supervision for staff wishing to develop competencies as CR therapists.